PENGARUH LATIHAN DRILLS MENGGIRING BOLA TERHADAP KEMAMPUANDRIBBLING TIM U15 SSB RAJAWALI PEKANBARU - Zulhamdani, Riza; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to know the influence of drills dribbling againts the ability dribbling team SSB Rajawali Pekanbaru. In this study researcher took population of the football SSB Rajawali Pekanbaru, amounting to 12 people, sampling using purposive sampling, “this sampling technique is based on the researches themselves”, The design of this study used one group pretest-posttest approach.TheInstrume performmed in this study to measure dribbling skils by dribbling test through obstacles. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05). The hypothesis proposed is the effect of exercise drills dribble of skills dribbling . Based on statistical data analysis, it yields pretest data Lcount 01468, data posttest Lcount 0,1361 and Ltabel 0,242, mean Lcount< Ltabel. Then the data is normally distributed. Based on t test analysis yielded Tcount equal to 9,93 and Ttabel 1,79, mean Tcount> Ttabel . Thus, we can concluded that there are Effect of drills drible against the ability dribbling team U15 SSB Rajawali Pekanbaru.Keywords: Drills dribble, Skill dribbling